Corset Trunkplasty: Recommended with Abdominal Skin Laxity and Open Cholecystectomy Scar. Issue 1 (January 2018) - Acevedo, Edwin; Nadhan, Kumar S.; Everett, Marc; Moya, Alexander; Bradley, James P.
Abstract : Background: Patients undergoing abdominoplasty with previous upper abdominal wall scars are at an increased risk for postoperative complications. The corset trunkplasty is a newer technique to treat abdominal wall laxity of the entire anterolateral abdomen while incorporating any previous open cholecystectomy scar. The authors performed a comparative outcomes study to determine whether the corset procedure would decrease the incidence of postoperative complications in patients with abdominal wall laxity and an open cholecystectomy scar when compared with traditional abdominoplasty. Methods: A retrospective study was performed on patients who underwent traditional and corset abdominoplasty. Patients were divided into four groups: traditional with scar, corset with scar, traditional no scar, and corset no scar. Evaluated metrics included procedure time, postoperative length of stay, complications, reoperations, and readmission rates. Results: Fifty-eight subjects were included in the study (traditional with scar, n = 15; corset with scar, n = 13; traditional no scar, n = 15; and corset no scar, n = 15). Demographics were similar among groups: body mass index, 33.7 kg/m 2 ; age, 44.3 years; and American Society of Anesthesiologists status, 2.5. The corset procedure took longer than the traditional method, regardless of whether a scar was present (146.1 minutes versus 125.7 minutes). However, the traditional with scar group had the greatest length of stay and higher complication, readmission, and reoperation rates. The corset with scar group had comparable outcomes to the corset no scar and traditional no scar groups. Conclusions: The corset trunkplasty procedure resulted in fewer adverse outcomes compared with traditional abdominoplasty in patients with previous open cholecystectomy scar. Its use should be considered in patients with significant abdominal wall laxity and existing upper abdominal surgical scars. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III. Abstract : Supplemental Digital Content is available in the text.